2019
DOI: 10.5897/ajbm2018.8725
|View full text |Cite
|
Sign up to set email alerts
|

The impact of intellectual capital on firms financial performance and market value: Empirical evidence from Italian listed firms

Abstract: The purpose of this paper is to extend the understanding of Intellectual Capital (IC) in the context of Italian listed firms. In this study, the Valued Added Intellectual Coefficient (VAIC) is employed as a measure of IC to investigate the relationship between IC, firms' financial performance and market value. The empirical investigation is developed by using data drawn from a sample of 135 Italian listed companies for the period from 2008 to 2017 and performing different Ordinary Least Squares (OLS) regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 20 publications
1
11
2
3
Order By: Relevance
“…These findings suggest that the manufacturing and service sectors in Tanzania have not utilized efficiently their human and capital. The findings are inconsistent with Forte et al (2019) who found out that only Human Capital efficiency shows a positive effect on firms' financial performance while Structural Capital efficiency and Capital Employed efficiency exhibit a negative effect. Further, the findings show that VAIC is significantly (p ≤ 0.05) and positively correlated with HCE, CEE, and SCE.…”
Section: Diagnostic Testscontrasting
confidence: 91%
See 3 more Smart Citations
“…These findings suggest that the manufacturing and service sectors in Tanzania have not utilized efficiently their human and capital. The findings are inconsistent with Forte et al (2019) who found out that only Human Capital efficiency shows a positive effect on firms' financial performance while Structural Capital efficiency and Capital Employed efficiency exhibit a negative effect. Further, the findings show that VAIC is significantly (p ≤ 0.05) and positively correlated with HCE, CEE, and SCE.…”
Section: Diagnostic Testscontrasting
confidence: 91%
“…The debate on IC is furthered by the growing desire by firms to increase investments not only in tangible assets but also in intangible assets Tran & Hong, 2020). Intangible assets are realized as, but not limited to, investments in copyrights, patents and goodwill, investments in the knowledge of staff, and relationships with key stakeholders (Asare et al, 2017;Forte et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…El capital relacional está fundamentalmente asociado al valor que generan las relaciones que la empresa entabla con su entorno, a través del intercambio de información y de productos a largo plazo con diferentes stakeholders, entre los que se incluyen: clientes, proveedores, socios aliados y accionistas (Ross et al, 2001;Forte, Matonti y Nicolò, 2019). Se trata pues de una dimensión externa a la organización, aunque en el valor de esas relaciones, como bien señala Sveiby (2018), influyen las acciones que desarrollan sus miembros, que son quienes las inician y mantienen.…”
Section: Marco Conceptual Y Normativounclassified